Employment Opportunities and Experiences among Recent Master's-Level Global Health Graduates - William Cherniak; Elahe Nezami; Quentin Eichbaum; Jessica Evert; Ashti Doobay-Persaud; Sharon Rudy; Ginny DeFrank; Tom Hall; Adam Hoverman (Ubiquity Press, 2019)
Objectives: To examine the job search, employment experiences, and job availability of recent global health-focused master's level graduates. Methods: An online survey was conducted from October to December 2016 based out of Washington, DC. The study sample includes students graduating with master's degrees in global health, public health with a global health concentration or global medicine from eight U.S. universities. Results: Out of 256 potential respondents, 152 (59%) completed the survey, with 102/152 (67%) employed. Of unemployed graduates, 38% were currently in another educational training program. Out of 91 employed respondents, 62 (68%) reported they had limitations or gaps in their academic training. The average salary of those employed was between $40,000 and $59,000 annually. The majority of respondents reported they currently work in North America (83.5%.); however, only 31% reported the desire to work in North America following graduation. Conclusions: Discrepancies exist between graduates' expectations of employment in global public health and the eventual job market. Communication between universities, students and employers may assist in curriculum development and job satisfaction for the global public health workforce.